2019
DOI: 10.3390/plants8100402
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Age, Canopy Position, and Habitat Affect the Carbon Isotope Discrimination and Water-Use Efficiency in Three C3 Leguminous Prosopis Species from a Hyper-Arid Climate

Abstract: The present study involved measurements of the stable carbon isotope composition (δ13C) and intrinsic water-use efficiency (iWUE) of three C3 leguminous Prosopis spp. (P. juliflora, P. cineraria, and P. pallida) foliage at different canopy positions (east and west) from saline (SLH) and non-saline habitats (NSH). Integrated measurements of the stable carbon isotope composition (δ13C) of plant tissue were broadly used to study iWUE, taking into consideration the effect of leaf age and canopy position on C isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…It is a typical phenomenon of plants affected by environmental stresses that showed a restricted supply of CO 2 as well as reduced activity of RuBisCO. These processes leads to reduced photosynthesis, carbon assimilation, growth and yield of the plants [ 16 , 51 , 52 , 53 , 54 ]. Previously published data showed that the small panicle length, chlorophyll concentrations, number of productive tillers, and lower number of primary branches per panicle were responsible factors in the low yield of quinoa [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a typical phenomenon of plants affected by environmental stresses that showed a restricted supply of CO 2 as well as reduced activity of RuBisCO. These processes leads to reduced photosynthesis, carbon assimilation, growth and yield of the plants [ 16 , 51 , 52 , 53 , 54 ]. Previously published data showed that the small panicle length, chlorophyll concentrations, number of productive tillers, and lower number of primary branches per panicle were responsible factors in the low yield of quinoa [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors indicated that it is extremely difficult to separate the growth and physiological secondary effects afrom the primary impacts caused by allelochemicals. However, the secondary impacts led to the disruption of cell differentiation, plant water status, water uptake, respiration, signal transduction, photosynthesis and enzyme function [ 3 , 6 , 7 , 10 , 17 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prosopis juliflora has typically invaded areas in Africa and the Arabian Peninsula where water table is close to the ground surface, such as gravel deserts, open plains, sand sheets, rivers and flood plains, wadies, and edges of farms [19][20][21][22]. In Saudi Arabia, P. juliflora was reported as a ruderal plant, mostly found inside the urban and suburban areas but also other natural areas on the mainlands and islands of the region and is the most prominent invasive species in majority of lowlands [22].…”
Section: History Of P Juliflora In African and Arabian Peninsulamentioning
confidence: 99%